Optimizing Water Hyacinth Drying Process Using DMAIC and Taguchi Method to Minimize Defects and Enhance Quality - Islahudin, Nur Islahudin; Nur Fazri, Ahmad Nur Fazri (JURNAL TEKNIK INDUSTRI, 2025)
This study aims to identify the causes of defects and design risk control strategies. The DMAIC method (Define, Measure, Analyze, Improve, Control) is employed as a data-driven approach within the Lean Manufacturing concept, aiming to find the optimal combination of settings and minimize defective products to maintain high quality, utilizing the Taguchi Method. The data used in this study are defective product data and water hyacinth drying experimental data at Bengok Craft UMKM in Semarang Regency. Furthermore, the data is processed using several methods, including Pareto diagrams, fishbone diagrams, Taguchi Method, and Analysis of Variance (ANOVA). This experiment tested three drying conditions: 100°C, 120°C, and 140°C, for 2, 3, and 4 hours, respectively. The results showed that the water hyacinth moisture content decreased with increasing temperature, reaching 56.25% at 140°C after a 4-hour drying time at 120°C. Among the tested conditions, 140°C was found to be the optimal temperature, resulting in water hyacinth with superior characteristics.